Composite sheets, laminates, and method for preventing surface delamination of structures
Patent Information
- Application Number
- JP2024000187
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-05-21
- Filing Date
- 2024-01-04
- Publication Date
- 2025-03-19
- Estimated Expiration
- 2042-05-18
AI Technical Summary
Existing peeling prevention layers for structures lack sufficient strength, elongation, and transparency, making it difficult to detect surface deformations and cracks while maintaining structural integrity.
A composite sheet comprising a cured adhesive and a glass fiber sheet with specific tensile modulus and basis weight, combined with a primer layer, to form a laminate that enhances strength, elongation, and visibility.
The composite sheet provides a peel-off prevention layer with improved strength, elongation, and visibility, allowing for effective detection of surface deformations and cracks while preventing material peeling.
Abstract
Description
[Technical field]
[0001] The present invention relates to a peel-preventing composite sheet, a laminate containing the same, and a method for preventing surface peeling of a structure using the same. [Background technology]
[0002] Conventionally, various measures have been taken to prevent materials from spalling from structures such as tunnels and bridges. For example, Patent Document 1 describes a method for preventing concrete spalling, characterized by forming a high-strength coating film on the concrete surface. Patent Document 2 describes a reinforcement coating method for reinforcing the surface of a concrete structure by forming a coating layer containing a continuous glass fiber sheet. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-15329 A [Patent Document 2] JP 2010-1707 A Summary of the Invention [Problem to be solved by the invention]
[0004] The peeling prevention layer formed on a structure is required to have sufficient strength and extensibility from the standpoint of retaining peeled pieces and making it easy to detect when peeling occurs.
[0005] On the other hand, the peel-preventing layer is also required to have a certain degree of transparency in order to observe the surface deformation, cracks, etc. of the structure. However, if the amount of reinforcing fibers such as glass fibers is increased to improve the strength and extensibility, the transparency of the peel-preventing layer decreases, making it difficult to visually observe the surface of the structure below the peel-preventing layer.
[0006] Therefore, an object of the present invention is to provide a composite sheet capable of forming a peeling-prevention layer having excellent strength, extensibility, and visibility to a substrate, and a laminate including the composite sheet, and a method for preventing surface peeling of a structure using the composite sheet. [Means for solving the problem]
[0007] One aspect of the present invention is a composite sheet for preventing peeling that is placed on a surface of a structure, the composite sheet comprising a cured adhesive and a glass fiber sheet, the cured adhesive having a tensile modulus of elasticity of 150 to 2700 MPa, and the glass fiber sheet having a basis weight of 150 to 350 g / m 2 The present invention relates to a composite sheet,
[0008] In one embodiment, the adhesive may be an epoxy adhesive.
[0009] A composite sheet according to one embodiment may include the above-mentioned glass fiber sheet and a cured product of the above-mentioned adhesive impregnated into the glass fiber sheet.
[0010] In one embodiment, the adhesive may be a two-component adhesive including a first component containing an epoxy compound and a second component containing a curing agent, and the cured product may be a cured product of a mixture of the first component and the second component.
[0011] The composite sheet according to one embodiment may have a spectral transmittance of 30% or more in the range of 380 to 780 nm.
[0012] Another aspect of the present invention relates to a laminate for preventing peeling that is placed on a surface of a structure, the laminate comprising an undercoat layer formed from a primer and the above-mentioned composite sheet.
[0013] In one embodiment, the primer has a bending strength of 2 N / mm2 as measured in accordance with the NEXCO test method for crack-impregnated materials. 2 The primer may be one having the above structure.
[0014] Yet another aspect of the present invention relates to a method for preventing surface spalling of a structure, comprising the step of placing the above-mentioned composite sheet on a surface of the structure.
[0015] In one embodiment, the positioning step may include a coating film forming step of forming a coating film containing the adhesive and the glass fiber sheet on the surface of the structure, and a sheet forming step of curing the coating film to form the composite sheet on the surface of the structure.
[0016] The method according to one embodiment may further include a pretreatment step of applying a primer onto the surface of the structure to form an undercoat layer, and in this case, the placing step may be a step of placing the above-mentioned composite sheet on the undercoat layer.
[0017] The present invention relates to, for example, the following <1> ~ <10> Regarding. <1> A peel-preventing composite sheet to be placed on a surface of a structure, The adhesive includes a cured body and a glass fiber sheet, The tensile modulus of the cured body is 150 to 2700 MPa, The weight of the glass fiber sheet is 150 to 350 g / m 2 A composite sheet. <2> The adhesive is an epoxy adhesive. <1> The composite sheet according to claim 1. <3> The glass fiber sheet and a cured product of the adhesive impregnated into the glass fiber sheet are included. <1> or <2> The composite sheet according to claim 1. <4> The adhesive is a two-component adhesive including a first component containing an epoxy compound and a second component containing a curing agent, The cured product is a cured product of a mixture of the first agent and the second agent. <1> ~ <3> 2. The composite sheet according to claim 1 . <5> The spectral transmittance in the range of 380 to 780 nm is 30% or more. <1> ~ <4> 2. The composite sheet according to claim 1 . <6> A peel-off prevention laminate to be placed on a surface of a structure, An undercoat layer formed by a primer; <1> ~ <5> and the composite sheet according to any one of the preceding claims. <7> The primer has a bending strength of 2N / mm2 as measured in accordance with the NEXCO test method for crack-impregnated materials. 2 This is the primer that <6> The laminate according to claim 1. <8> On the surface of the structure <1> ~ <5> 2. A method for preventing surface peeling of a structure, comprising the step of arranging the composite sheet according to any one of claims 1 to 11. <9> The placing step comprises: a coating film forming step of forming a coating film containing the adhesive and the glass fiber sheet on a surface of the structure; a sheet forming step of curing the coating film to form the composite sheet on the surface of the structure; Including, <8> The method according to <10> The method further includes a pretreatment step of applying a primer onto a surface of the structure to form an undercoat layer; The step of disposing includes <1> ~ <5> A step of placing the composite sheet according to any one of the above. <8> or <9> The method according to Effect of the Invention
[0018] According to the present invention, there is provided a composite sheet capable of forming a peeling-prevention layer excellent in strength, extensibility, and base visibility. Also, according to the present invention, there is provided a laminate including the composite sheet, and a method for preventing surface peeling of a structure using the composite sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Preferred embodiments of the present invention will now be described in detail.
[0020] (Composite sheet) The composite sheet of this embodiment is a peel-preventing composite sheet to be placed on the surface of a structure, and includes a cured adhesive and a glass fiber sheet. In the composite sheet of this embodiment, the tensile modulus of the cured adhesive is 150 to 2700 MPa, and the basis weight of the glass fiber sheet is 150 to 350 g / m 2 It is.
[0021] According to the composite sheet of the present embodiment, it is possible to form a peeling-prevention layer that is excellent in strength, extensibility, and visibility of the substrate.
[0022] The reason why the composite sheet of the present embodiment provides the above-mentioned effects is not particularly limited, but the following reasons are considered. 2 In addition, the composite sheet of the present embodiment uses an adhesive having a low tensile modulus of elasticity after curing, which reduces stress propagation and allows a large area to bear the load (i.e., the load per unit circumference can be kept low). 2 Even if the weight of the glass fiber sheet is kept below 350 g / m, excellent elongation is ensured. 2 Since the thickness is less than or equal to the thickness of the substrate, sufficient visibility of the substrate is ensured.
[0023] In the composite sheet of this embodiment, examples of adhesives include epoxy-based adhesives, urethane-based adhesives, silicone-based adhesives, acrylic-based adhesives, etc., and among these, epoxy-based adhesives are preferred from the viewpoint of superior adhesion to concrete surfaces, undercoat layers, glass fiber sheets, etc.
[0024] The form of the adhesive is not particularly limited, but may be, for example, a two-component adhesive. A preferred embodiment of the two-component adhesive will be described below.
[0025] <Two-component adhesive> A two-component adhesive according to one preferred embodiment includes a first component containing an epoxy compound and a second component containing a curing agent.
[0026] The two-component adhesive can form a hardened body by mixing the first and second components. That is, when a two-component adhesive is used, the hardened body of the adhesive can be said to be a hardened body of a mixture of the first and second components. The two-component adhesive may be provided, for example, as a two-component adhesive kit including a first component, a first container in which the first component is contained, a second component, and a second container in which the second component is contained, or may be provided as a two-component adhesive kit including a first component, a second component, and a container in which the first and second components are contained separately.
[0027] The two-part adhesive may be cold curing.
[0028] When using a two-component adhesive, it is preferable to mix the first and second components so that the ratio of the epoxy equivalent of the epoxy compound to the active hydrogen equivalent of the curing agent is 1:1, but the mixing ratio is not limited thereto. For example, the first and second components may be mixed so that the ratio of the active hydrogen equivalent of the curing agent to the epoxy equivalent of the epoxy compound is 0.5 to 1.5 (preferably 0.8 to 1.2). That is, the ratio of the active hydrogen equivalent of the curing agent to the epoxy equivalent of the epoxy compound may be, for example, 0.5 to 1.5, 0.5 to 1.2, 0.8 to 1.5, or 0.8 to 1.2.
[0029] The epoxy compound may be used alone or in combination of two or more. The epoxy compound may be a compound having one epoxy group or a compound having two or more epoxy groups. The epoxy compound preferably contains at least one compound having two or more epoxy groups.
[0030] The epoxy compound is preferably a compound having a glycidyl group as an epoxy group, that is, the epoxy compound preferably includes a compound having a glycidyl group, and more preferably includes a compound having two or more glycidyl groups.
[0031] Examples of epoxy compounds include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol A bis(polypropylene glycol glycidyl ether) ether, bisphenol A bis(polyethylene glycol glycidyl ether) ether, hydrogenated bisphenol A type epoxy resins, hydrogenated bisphenol F type epoxy resins, biphenyl type epoxy resins, urethane modified epoxy resins, rubber modified epoxy resins, alkyl glycidyl ethers, cresyl glycidyl ethers, phenyl glycidyl ethers, alkyl diglycidyl ethers, polyethylene glycol diglycidyl ethers, polypropylene glycol diglycidyl ethers, glycerin triglycidyl ethers, trimethylolpropane triglycidyl ethers, and the like.
[0032] A suitable example of the epoxy compound is a compound represented by the following formula (1-1). [ka]
[0033] In formula (1-1), p represents an integer of 0 or more, and R 11 and R 12 R each independently represents a hydrogen atom, an optionally substituted alkyl group having 1 to 5 carbon atoms, or an optionally substituted phenyl group. 11 When there are multiple R 11 may be the same or different. 12 When there are multiple R 12 may be the same or different from each other.
[0034] R 11 and R 12 Examples of the substituent that the alkyl group having 1 to 5 carbon atoms may have include a fluorine atom and an alkoxy group (for example, an alkoxy group having 1 to 5 carbon atoms), and a fluorine atom is preferred.
[0035] R 11 and R 12Examples of the substituent that the phenyl group in the formula (I) may have include a fluorine atom, an alkyl group (eg, an alkyl group having 1 to 5 carbon atoms), and an alkoxy group (eg, an alkoxy group having 1 to 5 carbon atoms).
[0036] R 11 R is preferably a group selected from the group consisting of a hydrogen atom, a methyl group, a phenyl group, and a trifluoromethyl group, more preferably a group selected from the group consisting of a hydrogen atom and a methyl group, and even more preferably a methyl group. 11 When there are multiple R 11 may be the same or different, and are preferably the same.
[0037] R 12 R is preferably a group selected from the group consisting of a hydrogen atom, a methyl group, a phenyl group, and a trifluoromethyl group, more preferably a group selected from the group consisting of a hydrogen atom and a methyl group, and even more preferably a methyl group. 12 When there are multiple R 12 may be the same or different, and are preferably the same.
[0038] R 11 and R 12 may be the same or different, and are preferably the same.
[0039] p is preferably 0 to 30, more preferably 0 to 20, and further preferably 0 to 2.
[0040] Another suitable example of the epoxy compound is a compound represented by the following formula (2-1). [ka]
[0041] In formula (2-1), n and m each independently represent an integer of 0 or more (preferably an integer of 1 or more); 1 and R 2 each independently represents a hydrogen atom or a methyl group; R3 and R 4 each independently represents a hydrogen atom, an optionally substituted alkyl group having 1 to 5 carbon atoms, or an optionally substituted phenyl group.
[0042] R 1 is preferably a methyl group. 1 When there are multiple R 1 may be the same or different, and are preferably the same.
[0043] R 2 is preferably a methyl group. 2 When there are multiple R 2 may be the same or different, and are preferably the same.
[0044] R 3 and R 4 Examples of the substituent that the alkyl group having 1 to 5 carbon atoms may have include a fluorine atom and an alkoxy group (for example, an alkoxy group having 1 to 5 carbon atoms), and a fluorine atom is preferred.
[0045] R 3 and R 4 Examples of the substituent that the phenyl group in the formula (I) may have include a fluorine atom, an alkyl group (eg, an alkyl group having 1 to 5 carbon atoms), and an alkoxy group (eg, an alkoxy group having 1 to 5 carbon atoms).
[0046] R 3 is preferably a group selected from the group consisting of a hydrogen atom, a methyl group, a phenyl group, and a trifluoromethyl group, more preferably a group selected from the group consisting of a hydrogen atom and a methyl group, and even more preferably a methyl group.
[0047] R 4 is preferably a group selected from the group consisting of a hydrogen atom, a methyl group, a phenyl group, and a trifluoromethyl group, more preferably a group selected from the group consisting of a hydrogen atom and a methyl group, and even more preferably a methyl group.
[0048] R 3 and R 4 may be the same or different, and are preferably the same.
[0049] Regarding n and m, n+m is preferably 2-20, and more preferably 2-11.
[0050] The curing agent may be any component capable of reacting with the epoxy compound and curing the mixture of the first agent and the second agent. The curing agent may be, for example, a compound having two or more reactive sites capable of reacting with the epoxy group in the epoxy compound. The curing agent may be used alone or in combination of two or more.
[0051] The curing agent is preferably an amine-based curing agent.
[0052] The amine-based curing agent is preferably an amine compound having a group selected from the group consisting of a primary amino group and a secondary amino group. The primary amino group of the amine compound is a group represented by -NH2. The secondary amino group of the amine compound is a group represented by -NH-. The amine-based curing agent may be, for example, a compound having one or more primary amino groups, a compound having two or more secondary amino groups, etc.
[0053] The amine-based curing agent may be, for example, at least one selected from the group consisting of an aliphatic amine, an alicyclic amine, a modified aliphatic polyamine, a modified alicyclic amine, and a polyamidoamine, and is preferably at least one selected from the group consisting of a modified aliphatic polyamine, a modified alicyclic amine, and a polyamidoamine.
[0054] The active hydrogen equivalent of the amine-based curing agent may be, for example, 20 or more, preferably 50 or more, more preferably 70 or more. This makes it easier to reduce the amount of nitrogen element in the adhesive, and makes it easier to obtain a cured body with a low amount of nitrogen element. The active hydrogen equivalent of the amine-based curing agent may be, for example, 200 or less, preferably 150 or less, more preferably 120 or less, and may be 100 or less. This tends to form a denser crosslinked structure, and to further improve the heat resistance and durability of the cured body. That is, the active hydrogen equivalent of the amine-based curing agent may be, for example, 20 to 200, 20 to 150, 20 to 120, 20 to 100, 50 to 200, 50 to 150, 50 to 120, 50 to 100, 70 to 200, 70 to 150, 70 to 120, or 70 to 100.
[0055] The active hydrogen equivalent of an amine curing agent indicates the mass (g) of the amine curing agent per mole of active hydrogen. When two or more amine curing agents are used in combination, the amine equivalent of the amine curing agent is calculated from the total amount of the amine curing agent and the total number of active hydrogens.
[0056] In the two-component adhesive, at least one of the first and second components may contain a filler. The incorporation of the filler can increase the viscosity of the mixture of the first and second components and suppress dripping during coating formation.
[0057] As the filler, any known filler that is blended in a two-component adhesive can be used without any particular limitation. Examples of the filler include organic fillers and inorganic fillers. In addition, the filler may be one that has been subjected to a surface treatment such as a hydrophobic treatment.
[0058] The shape of the filler is not particularly limited, and may be, for example, granular, flake-like, fibrous, emulsion-like, or the like.
[0059] The organic filler may be, for example, resin particles. The resin particles may be solid particles, porous particles, or hollow particles. The resin particles may be, for example, (meth)acrylic acid ester particles, polystyrene particles, etc.
[0060] Examples of inorganic fillers include fumed silica, calcium carbonate, talc, clay, metal oxides, metal hydroxides, silica, etc. The inorganic filler may be hollow particles, fibrous particles, solid particles, or porous particles thereof.
[0061] The filler is preferably an inorganic filler. An example of the inorganic filler is fumed silica. Fumed silica has a specific surface area of 70 g / m 2 or more (preferably 80 to 400 g / m 2 ) is preferred. The specific surface area means the BET specific surface area. The BET specific surface area indicates a value measured by a gas phase adsorption method in which gas molecules (nitrogen molecules) with a known occupied area are adsorbed on the surface of the inorganic filler, and the specific surface area is calculated from the amount of the adsorbed gas molecules.
[0062] As the inorganic filler, hydrophilic silica can be suitably used, and hydrophilic fumed silica is preferable as the hydrophilic silica.
[0063] The average particle size of the hydrophilic silica may be, for example, 1 nm or more, preferably 5 nm or more, more preferably 7 nm or more, and may be 9 nm or more or 10 nm or more. The average particle size of the hydrophilic silica may be, for example, 15 nm or less, or may be 14 nm or less. By using such hydrophilic silica, the viscosity of the mixture of the first agent and the second agent can be improved while maintaining high transparency of the cured body, and dripping during coating film formation can be efficiently suppressed. That is, the average particle size of the hydrophilic silica may be, for example, 1 to 15 nm, 1 to 14 nm, 5 to 15 nm, 5 to 14 nm, 7 to 15 nm, 7 to 14 nm, 9 to 15 nm, 9 to 14 nm, 10 to 15 nm, or 10 to 14 nm.
[0064] The hydrophilic silica preferably has a hydrophobicity of 30 or less, more preferably 20 or less, and even more preferably 10 or less, based on the methanol wettability. Here, the hydrophobicity refers to the volume fraction of methanol in a methanol-water mixed solution at the time when the silica is dispersed in water and all of the floating silica sinks by dropping methanol into the solution. The measurement can be performed, for example, by adding 0.2 g of silica to 50 ml of ion-exchanged water, dropping methanol from a burette while stirring with a magnetic stirrer. The floating silica gradually sinks, and the volume fraction of methanol in the methanol-water mixed solution at the end point when all of the floating silica sinks is the hydrophobicity.
[0065] The hydrophilic silica may be a commercially available product. Examples of the commercially available hydrophilic silica include AEROSIL 150, 200, 300, 380 (manufactured by Evonik), RHEOROSIL QS-10, QS-102, CP-102, QS-20, QS-20L, QS-30, QS-40 (manufactured by Tokuyama Corporation), WACKER HDK V15, N20, N20P, T30, T40 (manufactured by Asahi Kasei Wacker Silicone Co., Ltd.), etc.
[0066] The content of the filler in the two-component adhesive may be, for example, 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 1.0% by mass or more, and even more preferably 1.5% by mass or more, when the total amount of the solid content in the first agent and the second agent is taken as 100% by mass. This makes the thickening effect of suppressing dripping more pronounced. In addition, the content of the filler in the two-component adhesive may be, for example, 5.5% by mass or less, preferably 5.0% by mass or less, and more preferably 4.0% by mass or less, when the total amount of the solid content in the first agent and the second agent is taken as 100% by mass. This tends to further improve the transparency of the cured body. In other words, the content of the filler in the two-component adhesive may be, for example, 0.1 to 5.5 mass%, 0.1 to 5.0 mass%, 0.1 to 4.0 mass%, 0.5 to 5.5 mass%, 0.5 to 5.0 mass%, 0.5 to 4.0 mass%, 1.0 to 5.5 mass%, 1.0 to 5.0 mass%, 1.0 to 4.0 mass%, 1.5 to 5.5 mass%, 1.5 to 5.0 mass%, or 1.5 to 4.0 mass%, when the total amount of solids in the first and second components is taken as 100 mass%.
[0067] In the two-component adhesive, at least a part of the first and second components preferably contains a curing accelerator. The incorporation of a curing accelerator may improve the curing properties of the mixture of the first and second components.
[0068] The curing accelerator may be any one that can accelerate the reaction between the epoxy compound and the curing agent, and any known curing accelerator may be used without any particular limitation. As the curing accelerator, for example, a monophenol compound is preferably used. As the monophenol compound, 4-tert-butylphenol is preferable.
[0069] The content of the curing accelerator in the two-component adhesive may be, for example, 0.1% by mass or more, preferably 0.5% by mass or more, more preferably 1.0% by mass or more, when the total amount of the solids in the first and second agents is taken as 100% by mass. This tends to improve the curing property of the mixture of the first and second agents. In addition, the content of the curing accelerator in the two-component adhesive may be, for example, 5.5% by mass or less, preferably 5.0% by mass or less, more preferably 4.5% by mass or less, when the total amount of the solids in the first and second agents is taken as 100% by mass. This tends to suppress the remaining non-reactants and improve durability. In other words, the content of the curing accelerator in the two-component adhesive may be, for example, 0.1 to 5.5 mass%, 0.1 to 5.0 mass%, 0.1 to 4.5 mass%, 0.5 to 5.5 mass%, 0.5 to 5.0 mass%, 0.5 to 4.5 mass%, 1.0 to 5.5 mass%, 1.0 to 5.0 mass%, or 1.0 to 4.5 mass%, when the total amount of solids in the first and second parts is taken as 100 mass%.
[0070] The two-component adhesive may further contain other components in addition to those described above. Examples of the other components include a curing retarder, a light stabilizer, a light absorber, an antioxidant, an anti-deterioration agent, a pigment, a dye, a silane coupling agent, a defoamer, a leveling agent, a dispersant, a rheology control agent, a wax, a solvent, and water. Among these, the rheology control agent is preferred.
[0071] The rheology control agent suppresses dripping and improves the workability of the two-component adhesive. The rheology control agent is preferably an amide. Examples of the amide include higher fatty acid amides, polyamides, and amide oligomers. The amide is preferably a polyaminoamide.
[0072] The content of the rheology control agent in the two-component adhesive may be, for example, 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, even more preferably 0.5% by mass or more, and even more preferably 1.0% by mass or more, when the total amount of the solid contents in the first and second agents is taken as 100% by mass. This allows for a more pronounced thickening effect to suppress dripping. The content of the rheology control agent may be, for example, 7.0% by mass or less, preferably 5.0% by mass or less, and more preferably 3.0% by mass or less, when the total amount of the solid contents in the first and second agents is taken as 100% by mass. This tends to further improve the tensile properties. That is, the content of the rheology control agent in the two-component adhesive, when the total amount of solids in the first and second components is taken as 100 mass%, may be, for example, 0.01 to 7.0 mass%, 0.01 to 5.0 mass%, 0.01 to 3.0 mass%, 0.05 to 7.0 mass%, 0.05 to 5.0 mass%, 0.05 to 3.0 mass%, 0.1 to 7.0 mass%, 0.1 to 5.0 mass%, 0.1 to 3.0 mass%, 0.5 to 7.0 mass%, 0.5 to 5.0 mass%, 0.5 to 3.0 mass%, 1.0 to 7.0 mass%, 1.0 to 5.0 mass%, or 1.0 to 3.0 mass%.
[0073] The first agent contains an epoxy compound, and may contain a filler as necessary, and may further contain other components as necessary.
[0074] The content of the epoxy compound in the first agent may be, for example, 80 mass% or more, preferably 90 mass% or more, more preferably 95 mass% or more, and may be 100 mass% based on the total amount of solids in the first agent.
[0075] The second agent contains an amine-based curing agent, and may contain a filler as necessary, and may further contain other components as necessary.
[0076] The content of the amine-based curing agent in the second agent may be, for example, 60 mass% or more, preferably 80 mass% or more, more preferably 90 mass% or more, and may be 100 mass% based on the total amount of solids in the second agent.
[0077] In the two-component adhesive, the mixture of the first and second components preferably exhibits a viscosity of 2000 mPa·s or more and 100000 mPa·s or less (more preferably 4000 mPa·s or more and 50000 mPa·s or less, i.e., for example, 2000 to 100000 mPa·s, 2000 to 50000 mPa·s, 4000 to 100000 mPa·s, or 4000 to 50000 mPa·s) and a thixotropic index of 2.0 or more (more preferably 3.0 to 8.0, i.e., for example, 2.0 or more, 2.0 to 8.0, or 3.0 to 8.0). The viscosity and thixotropic index of the mixture of the first and second components change over time due to the reaction between the epoxy compound and the curing agent. In other words, the above definition means that the mixture of the first and second components exhibits the above viscosity and thixotropic index for a certain period of time after mixing.
[0078] In this specification, the viscosity of the mixture of the first and second agents refers to the viscosity measured by a cone-plate type rotational viscometer at 23° C. and 20 rpm. The thixotropic index refers to the ratio (V2 / V1) of the viscosity V2 measured by a cone-plate type rotational viscometer at 23° C. and 20 rpm to the viscosity V1 measured by a cone-plate type rotational viscometer at 23° C. and 2 rpm.
[0079] The cured adhesive preferably has a spectral transmittance of 30% or more per mm of thickness in the visible light region (380 to 780 nm). In this specification, the spectral transmittance of the cured adhesive is measured using a UV-VIS-NIR spectrophotometer SolidSpec-3700i manufactured by Shimadzu Corporation. This makes it easier to obtain a peeling prevention layer with better visibility of the base.
[0080] The tensile modulus of the cured adhesive is 150 MPa or more, preferably 300 MPa or more, more preferably 500 MPa or more, even more preferably 700 MPa or more, and even more preferably 1000 MPa or more. This tends to further improve the heat resistance of the cured adhesive. In addition, the tensile modulus of the cured adhesive is 2700 MPa or less, preferably 2500 MPa or less, and more preferably 2200 MPa or less. This makes the above-mentioned effects more pronounced, and tends to further improve the elongation, especially at low temperatures. That is, the tensile modulus of elasticity of the cured adhesive may be, for example, 150 to 2700 MPa, 150 to 2500 MPa, 150 to 2200 MPa, 300 to 2700 MPa, 300 to 2500 MPa, 300 to 2200 MPa, 500 to 2700 MPa, 500 to 2500 MPa, 500 to 2200 MPa, 700 to 2700 MPa, 700 to 2500 MPa, 700 to 2200 MPa, 1000 to 2700 MPa, 1000 to 2500 MPa, or 1000 to 2200 MPa.
[0081] The tensile strength of the cured adhesive is not particularly limited, and may be, for example, 5 MPa or more, preferably 10 MPa or more, and more preferably 20 MPa or more. This tends to further improve the heat resistance of the cured adhesive. The tensile strength of the cured adhesive may be, for example, 80 MPa or less, 60 MPa or less, or 40 MPa or less. That is, the tensile strength of the cured adhesive may be, for example, 5 to 80 MPa, 5 to 60 MPa, 5 to 40 MPa, 10 to 80 MPa, 10 to 60 MPa, 10 to 40 MPa, 20 to 80 MPa, 20 to 60 MPa, or 20 to 40 MPa.
[0082] <Glass fiber sheet> The composite sheet of this embodiment comprises a fiberglass sheet.
[0083] The composition of the glass constituting the glass fiber sheet is not particularly limited, and may be, for example, E glass, AR glass, S glass, C glass, D glass, ECR glass, or the like.
[0084] The fineness of the glass fiber sheet may be, for example, 50 tex or more, preferably 70 tex or more, and more preferably 130 tex or more. This makes it easier for openings to form between the fibers, makes it easier for the adhesive to be impregnated, and improves workability during the production of the composite sheet. The fineness of the glass fiber sheet may be, for example, 1500 tex or less, preferably 1000 tex or less, and more preferably 500 tex or less. This increases the fiber density and improves the handleability. That is, the fineness of the glass fiber sheet may be, for example, 50 to 1500 tex, 50 to 1000 tex, 50 to 500 tex, 70 to 1500 tex, 70 to 1000 tex, 70 to 500 tex, 130 to 1500 tex, 130 to 1000 tex, or 130 to 500 tex.
[0085] The composite sheet of this embodiment can be manufactured, for example, by a manufacturing method including a coating step of applying an adhesive (e.g., a mixture of a first agent and a second agent) to a glass fiber sheet to form a coating film, and a curing step of curing the coating film.
[0086] Moreover, the composite sheet of the present embodiment can also be produced by a production method including, for example, a step of arranging a glass fiber sheet on a coating of an adhesive, and a step of curing the coating.
[0087] In the application step, the glass fiber sheet may be partially or entirely impregnated with the adhesive, or the application step may be a step of applying the adhesive to the glass fiber sheet placed on the surface of the structure.
[0088] In the coating process, the amount of adhesive applied is, for example, 200 g / m 2 or more, preferably 400 g / m 2 More preferably, 500 g / m 2 The amount of adhesive applied is, for example, 1500 g / m 2 or less, preferably 1000 g / m 2 Less than 700g / m 2This makes it easier to obtain a composite sheet in which the content of the cured adhesive falls within the preferred range described below. That is, the amount of adhesive applied is, for example, 200 to 1500 g / m 2 , 200~1000g / m 2 , 200~700g / m 2 , 400~1500g / m 2 , 400~1000g / m 2 , 400~700g / m 2 , 500~1500g / m 2 , 500~1000g / m 2 , or 500~700g / m 2 It may be.
[0089] In the placing step, the glass fiber sheet may be impregnated with a part or all of the adhesive, or the placing step may be a step of placing the glass fiber sheet on a coating of the adhesive formed on the surface of the structure.
[0090] The curing step may be, for example, a step of curing a coating of the adhesive by heating. The heating temperature may be appropriately set depending on the types of adhesive and curing agent, etc.
[0091] In the composite sheet of this embodiment, the weight of the glass fiber sheet is 150 g / m 2 or more, preferably 170 g / m 2 More preferably, 200 g / m 2 This makes it easier to obtain a peeling prevention layer having superior strength and elongation. In addition, the weight of the glass fiber sheet is 350 g / m 2 less than 300 g / m 2 Less than 250 g / m 2 This makes it easier to obtain a peeling prevention layer having better visibility of the substrate. That is, the weight of the glass fiber sheet is, for example, 150 to 350 g / m 2 , 150~300g / m 2 , 150~250g / m 2 , 170~350g / m 2 , 170~300g / m 2 , 170~250g / m2 , 200~350g / m 2 , 200~300g / m 2 , or 200~250g / m 2 It may be.
[0092] In the composite sheet of this embodiment, the content of the cured adhesive is, for example, 200 g / m 2 or more, preferably 400 g / m 2 More preferably, 500 g / m 2 This improves the surface smoothness of the composite sheet, making it easier to obtain a peeling prevention layer with better visibility of the substrate. The content of the cured adhesive is, for example, 1500 g / m 2 or less, preferably 1000 g / m 2 Less than 700g / m 2 This tends to reduce the amount of harmful substances generated when the cured body is burned. That is, the content of the cured body in the adhesive is, for example, 200 to 1500 g / m 2 , 200~1000g / m 2 , 200~700g / m 2 , 400~1500g / m 2 , 400~1000g / m 2 , 400~700g / m 2 , 500~1500g / m 2 , 500~1000g / m 2 , or 500~700g / m 2 It may be.
[0093] The thickness of the composite sheet is not particularly limited, but may be, for example, 0.25 mm or more, preferably 0.4 mm or more, and more preferably 0.5 mm or more. The thickness of the composite sheet may be, for example, 1.6 mm or less, preferably 1.2 mm or less, and more preferably 0.8 mm or less. That is, the thickness of the composite sheet may be, for example, 0.25 to 1.6 mm, 0.25 to 1.2 mm, 0.25 to 0.8 mm, 0.4 to 1.6 mm, 0.4 to 1.2 mm, 0.4 to 0.8 mm, 0.5 to 1.6 mm, 0.5 to 1.2 mm, or 0.5 to 0.8 mm.
[0094] The composite sheet of this embodiment has a spectral transmittance in the visible light region (380 to 780 nm) of, for example, 30% or more, preferably 40% or more, more preferably 50% or more, even more preferably 60% or more, and even more preferably 70% or more. This makes it easier to obtain a peeling prevention layer with better undercoat visibility. In this specification, the spectral transmittance of the composite sheet is measured using a UV-VIS-NIR spectrophotometer SolidSpec-3700i manufactured by Shimadzu Corporation.
[0095] The composite sheet of the present embodiment is placed on the surface of a structure to prevent concrete pieces and the like from peeling off from the surface of the structure. A layer other than the composite sheet may be further formed on the surface of the structure. That is, a laminate of the composite sheet and another layer may be formed on the surface of the structure.
[0096] The laminate may be, for example, a laminate including an undercoat layer formed from a primer and a composite sheet.
[0097] The primer has a bending strength of 2N / mm2, measured according to the NEXCO test method for crack-impregnated materials. 2 The primer may be one having the above structure.
[0098] The viscosity of the primer is not particularly limited, but may be, for example, 100 mPa·s or more, preferably 200 mPa·s or more, and more preferably 400 mPa·s or more. This tends to prevent absorption into the base and facilitate coating film formation. The viscosity of the primer may be, for example, 4000 mPa·s or less, preferably 2000 mPa·s or less, and more preferably 1000 mPa·s or less. This tends to further improve impregnation into cracks on the surface of the structure. That is, the viscosity of the primer may be, for example, 100 to 4000 mPa·s, 100 to 2000 mPa·s, 100 to 1000 mPa·s, 200 to 4000 mPa·s, 200 to 2000 mPa·s, 200 to 1000 mPa·s, 400 to 4000 mPa·s, 400 to 2000 mPa·s, or 400 to 1000 mPa·s.
[0099] Examples of the primer include an epoxy-based primer, a urethane-based primer, an acrylic-based primer, etc. Among these, an epoxy-based primer is preferred from the viewpoint of excellent adhesion to the surface of a structure.
[0100] In addition, a layer formed from an impregnating reinforcing material, a cross-section repair agent, a leveling material, etc. may be further formed on the surface of the structure. That is, the laminate may further include a layer formed from an impregnating reinforcing material, a cross-section repair agent, a leveling material, etc.
[0101] According to the composite sheet of the present embodiment, a peeling-preventing layer having excellent strength, extensibility and visibility of the substrate can be formed. The peeling-preventing layer may be, for example, a layer made of the above-mentioned laminate.
[0102] (Method of preventing surface peeling of structures) A method for preventing spalling of a structure may include disposing a composite sheet as described above on a surface of the structure.
[0103] The positioning step may include a coating film forming step of forming a coating film containing an adhesive and a glass fiber sheet on the surface of the structure, and a sheet forming step of curing the coating film to form a composite sheet on the surface of the structure.
[0104] The coating film forming step may be, for example, a step of placing a glass fiber sheet on the surface of a structure and applying an adhesive onto the glass fiber sheet to form a coating film.
[0105] The coating film forming step may also be a step of applying an adhesive onto the surface of a structure, and then placing a glass fiber sheet on the applied adhesive to form a coating film.
[0106] The above method may further include a pretreatment step of applying a primer onto the surface of the structure to form an undercoat layer. When the pretreatment step is included, the coating film forming step may be a step of forming a coating film on the undercoat layer.
[0107] The above method may further include a topcoat step of forming a topcoat layer on the composite sheet. As the topcoat layer, any topcoat layer used for a known anti-peeling layer may be used without any particular limitation. The topcoat layer may be, for example, a protective coating, a topcoat layer, or the like.
[0108] The surface of the structure is not particularly limited, but a concrete surface or a mortar surface is preferred from the viewpoint of obtaining a significant effect of preventing the material from peeling off.
[0109] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to the above-described embodiments. EXAMPLES
[0110] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0111] The abbreviations for the components used in the examples and comparative examples, and the test methods used in the examples and comparative examples, are as follows:
[0112] <Epoxy compounds> ADEKA RESIN EP-4100 (EP4100 in the table): an epoxy compound having the structure of formula (1-1) (manufactured by ADEKA Corporation, epoxy equivalent 190, R 11 and R 12 is a methyl group) ADEKA RESIN EP-4005 (EP4005 in the table): an epoxy compound having the structure of formula (2-2) (manufactured by ADEKA CORPORATION, epoxy equivalent 510) ADEKA RESIN EP-4000 (referred to as "EP4000" in the table): an epoxy compound having the structure of formula (2-2) (manufactured by ADEKA CORPORATION, epoxy equivalent: 320) SY-OCG: Orthocresyl glycidyl ether (manufactured by Sakamoto Pharmaceutical Co., Ltd., epoxy equivalent 180) [ka] [In the formula, n and m each independently represent an integer of 1 or more.]
[0113] <Filler> ·AEROSIL 200 (AS200 in the table): Hydrophilic fumed silica (primary particle diameter 12 nm, BET specific surface area 200 g / m 2 , hydrophobicity 0%, manufactured by Evonik)
[0114] <Amine-based hardener> TOHMAID 235-A (235A in the table): Polyamidoamine (T&K TOKA, active hydrogen equivalent 95) Fujicure 8116 (8116 in the table): Modified alicyclic polyamine (T&K Toka, active hydrogen equivalent 72) · TOMAID 245-S (245-S in the table): Polyamidoamine (T&K TOKA, active hydrogen equivalent 80)
[0115] <Other ingredients> BYK R607: Polyaminoamide (rheology control agent (RC agent in the table), manufactured by BYK-Chemie Co., Ltd.)
[0116] <Glass fiber sheet> G1 (weight: 200g / m 2 , fineness: 135tex) G2 (weight: 184g / m 2 , fineness: 70tex) G3 (weight: 256g / m 2 , fineness: 135tex) G4 (weight: 300g / m 2 , fineness: 400tex) G5 (weight: 400g / m 2 , fineness: 600tex)
[0117] <Primer> P1 (epoxy primer, viscosity: 676 mPa·s, bending strength measured according to the NEXCO test method for crack-impregnated materials: 2.2 N / mm 2 ) P2 (epoxy primer, viscosity: 700 mPa·s, bending strength measured according to the NEXCO test method for crack-impregnated materials: 3.3 N / mm 2 ) P3 (epoxy primer, viscosity: 275 mPa·s) Flexural strength measured according to the NEXCO test method for crack-impregnated materials: 3.1 N / mm 2 )
[0118] <Tensile test of hardened adhesive> The first agent ((1) in the table) and the second agent ((2) in the table) were weighed and mixed as shown in Table 1, Table 2 or Table 3. Next, the mixture was poured into a formwork, cured at 23°C for 7 days, and then demolded. Tests were performed at an ambient temperature of 23°C and a tensile speed of 5 mm / min using a universal testing machine manufactured by A&D Co., Ltd. in accordance with JIS K7161 (Determination of tensile properties of plastics).
[0119] <Transmittance of composite sheet> An adhesive composition was obtained by weighing and mixing the first and second parts as shown in Table 1, Table 2, or Table 3. The first and second parts were mixed so that the ratio of epoxy equivalent to active hydrogen equivalent was 1:1. Next, a specified amount of coating (0.6 kg / m2) was applied onto the PET sheet. 2 ) and immediately after coating, a fiber sheet was placed on top and the fiber sheet was impregnated with the adhesive composition using a roller. After curing at 23°C for 7 days, the PET film was peeled off to obtain a composite sheet with a thickness of 0.6 mm. The spectral transmittance of the obtained composite sheet was measured in the range of 380 to 780 nm using a UV-VIS-NIR spectrophotometer SolidSpec-3700i manufactured by Shimadzu Corporation. The lowest value of the measured transmittance is shown in the table.
[0120] <Push-out test of composite sheet> A core of φ100mm was drilled from the center of a type 1 U-shaped gutter cover (cover) (400×600×60mm) (hereinafter referred to as "U-shaped cover") specified in JIS A5372 Appendix E using a concrete core drill. The core was drilled to a depth of 55±3.0mm from the opposite side of the construction surface. In a 23°C environment, the application surface is scraped and degreased with a disk sander, and then the first and second agents of the primer are measured out in the specified amounts, mixed, and applied in the specified amount (0.15 kg / m) using a roller. 2 ) and allowed to cure for one day. After curing, the first and second adhesive agents are weighed out in the specified amounts, mixed, and applied in the specified amount (0.60 kg / m2) using a rubber spatula. 2 ), immediately attached a fiber sheet, impregnated with a roller, smoothed the surface with a rubber spatula, and then left to cure for 7 days. After curing, a load was applied to the center of the core at 1 mm / min in accordance with JSCE-K533, and after the core broke, a load was applied at 5 mm / min to measure the maximum load and the displacement at that time.
[0121] <Base visibility> A crack scale simulating a 0.5 mm wide crack was attached to a mortar (70 × 150 × 10 mm) prepared according to JIS R 5201. Then, the first and second agents of the primer were weighed out in the specified amounts, mixed, and applied with a roller in the specified amount (0.15 kg / m 2 ) and allowed to cure for one day. After curing, the first and second adhesive agents are weighed out in the specified amounts, mixed, and applied in the specified amount (0.60 kg / m2) using a rubber spatula. 2 ), immediately attached a fiber sheet, impregnated with a roller, smoothed the surface with a rubber spatula, and then left to cure for 7 days. After curing, the cracks in the crack scale were visually observed and evaluated. If they were visible, they were rated A, and if they were not visible, they were rated B.
[0122] Example 1 An adhesive composition was obtained by mixing the first and second parts having the compositions shown in Table 1. The obtained adhesive composition was subjected to a tensile test of the cured product by the above-mentioned method. Next, a composite sheet was produced and evaluated by the above-mentioned method using the glass fiber sheet shown in Table 1. The results are shown in Table 1.
[0123] (Examples 2 to 12, Comparative Examples 1 to 2) Adhesive compositions were prepared in the same manner as in Example 1, except that the compositions of the first and second agents were changed as shown in Table 1, Table 2 or Table 3, and tensile tests of the cured products were carried out by the above-mentioned method. Next, using the obtained adhesive composition, composite sheets were produced and evaluated in the same manner as in Example 1, except that the glass fiber sheet and primer shown in Table 1, Table 2 or Table 3 were used. The results are shown in Table 1, Table 2 or Table 3.
[0124] [Table 1]
[0125] [Table 2]
[0126] [Table 3]
Claims
1. A peel-preventing composite sheet to be placed on a surface of a structure, The adhesive includes a cured body and a glass fiber sheet, The tensile modulus of the cured body is 150 to 2700 MPa; The weight of the glass fiber sheet is 150 to 350 g / m 2 A composite sheet.
2. The composite sheet of claim 1 , wherein the adhesive is an epoxy adhesive.
3. The composite sheet according to claim 1 , comprising: the glass fiber sheet; and a cured product of the adhesive impregnated into the glass fiber sheet.
4. The adhesive is a two-component adhesive including a first component containing an epoxy compound and a second component containing a curing agent, The composite sheet according to claim 1 , wherein the cured product is a cured product of a mixture of the first agent and the second agent.
5. 2. The composite sheet according to claim 1, which has a spectral transmittance of 30% or more in the range of 380 to 780 nm.
6. A peel-off prevention laminate to be placed on a surface of a structure, A laminate comprising an undercoat layer formed by a primer and the composite sheet according to any one of claims 1 to 5.
7. A method for preventing surface peeling of a structure, comprising a step of placing the composite sheet according to any one of claims 1 to 5 on a surface of the structure.
8. The placing step comprises: a coating film forming step of forming a coating film containing the adhesive and the glass fiber sheet on a surface of the structure; a sheet forming step of curing the coating film to form the composite sheet on the surface of the structure; The method of claim 7, comprising:
9. The method further includes a pretreatment step of applying a primer onto a surface of the structure to form an undercoat layer; The method of claim 7 , wherein the disposing step comprises disposing the composite sheet onto the primer layer.